Performance Evaluation of Classification Algorithms for Parkinson’s Disease Diagnosis: A Comparative Study - Baruah, Dhiraj; Rehman, Rizwan; Bora, Pranjal Kumar; Mahanta, Priyakshi; Dutta, Kankana; Konwar, Pinakshi (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2025)
Selection and implementation of classification algorithms along with proper preprocessing methods are important for the accuracy of predictive models. This paper compares some well-known and frequently used algorithms for classification tasks and performs in depth analysis. In this study we analyzed four most frequently used algorithm viz random forest (RF), decision tree (DT), logistic regression (LR) and support vector machine (SVM). To conduct the study on the well-known Oxford Parkinson’s disease Detection dataset obtained from the UCI Machine Learning Repository. We evaluated the algorithms' performance using six distinct approaches. Firstly, we used the classifiers where we didn’t used any method to enhance the performance of the classifier. Secondly, we applied Principal Component Analysis (PCA) to minimize the dimensionality of the dataset. Thirdly, we used collinearity-based feature elimination (CFE) method where we applied correlation among the features and if the correlation between a pair of features exceeds the threshold of 0.9, we eliminated one from the pair. Fourthly, we adopt synthetic minority oversampling technique (SMOTE) to synthetically increase the instances of the minority class. Fifth, we combined PCA+SMOTE and on sixth method, we combined CFE + SMOTE. The study demonstrates that SVM is highly effective for Parkinson’s disease classification. SVM maintained high accuracy, precision, recall and F1-score across various preprocessing techniques including PCA, CFE and SMOTE, making it robust and reliable for clinical applications. RF showed improved results with SMOTE. However, it experienced reduced performance with PCA and CFE, indicating its dependence on original feature interactions. DT benefited from PCA, while LR showed limited improvements and sensitivity to oversampling. These findings emphasize the importance of selecting appropriate preprocessing techniques to enhance model performance.